Corporate governance, legal systems and value relevance of fair value estimates. Empirical evidence from the EU banking sector. Issue 2 (3rd April 2019) - Mechelli, Alessandro; Cimini, Riccardo
ABSTRACT: Scholars agree that the role played by corporate governance mechanisms is likely to be affected by the quality of the legal systems in which firms operate. This paper investigates whether the quality of firm-level corporate governance is more valuable in countries with a high- or low-quality legal system. To do so, the paper focuses on the value relevance of fair value hierarchy disclosed by the European financial entities listed in 14 stock markets over the period 2011–2015. Findings show that differences in the quality of legal systems positively affect the value relevance of fair value estimates and provide evidence that the effect of firm-level corporate governance on the value relevance of fair value assets and liabilities is stronger in countries with high-quality legal systems. Our study contributes to the literature to the extent to which it shows that the ability of corporate governance to improve the value relevance of fair value measurements depends on the quality of the legal system under which firms operate. For this reason, our results complement findings reported by prior studies that have separately investigated the effect of the quality of corporate governance and of investor protection on the value relevance of fair value measurement.